Colorimetric assay of l-cysteine based on peroxidase-mimicking DNA-Ag/Pt nanoclusters - Wu, Liang-Liang; Wang, Li-Ying; Xie, Zheng-Jun; Pan, Na; Peng, Chi-Fang (Sensors and actuators. B, Chemical, 2016)
This paper reported that the peroxidase-like activity of DNA-Ag/Pt nanoclusters (NCs) can be inhibited significantly by l-cysteine. Based on this finding, a highly sensitive and selective colorimetric detection for l-cysteine was developed with a detection limit (LOD) of 2.0nM and a linear range from 5.0nM to 500nM. This detection for l-cysteine was highly selectivity over other amino acids. The high sensitivity and selectivity of this method facilitated the detection of l-cysteine in biological samples. Moreover, this method developed here was low-cost and simple. These results indicated the excellent analytical application of Ag/Pt NCs as enzyme mimic.